Karakterisasi Ekstrak Kurkumin dari Kunyit Putih (Kaemferia rotunda L.) dan Kunyit Kuning (Curcuma domestica Val.) - Nura Malahayati; Tri Wardhani Widowati; Anita Febrianti (agriTECH, 2021)
This study was aimed to identify the chemical characteristics of white and yellow turmeric powder, and to investigate the influence of both types with three different solvents on yield, total phenolic content, curcuminoid, antioxidant, and antibacterial activity of curcumin crude extract. The curcumin extraction was performed by maceration using N-hexane, ethyl acetate, and ethanol solvents. The results showed that the proximate analysis excluding carbohydrate content of white turmeric powder were lower compared to the yellow type. Curcumin crude extract of white turmeric powder had lower yield, total phenolic content, curcuminoid, antioxidant, and antibacterial activity compared to yellow turmeric extract. Moreover, turmeric extracted with ethyl acetate had higher total phenolic, curcuminoid, antioxidant, and antibacterial activity compared to turmeric extracted using N-hexane and ethanol. Based on the highest total phenolic (193.26 mg GAE/kg) and curcuminoid content (8.13 mg/L), the best treatment was yellow turmeric extract using ethyl acetate solvent. This treatment had the lowest IC50 (63.38 μg/ mL), and the highest clear zone size of S. aureus (6.59 mm) and E. coli (6.29 mm) at concentration of 2000 ppm.